A Fifty‐Two–Week, Randomized, Placebo‐Controlled Trial of Certolizumab Pegol in Nonradiographic Axial Spondyloarthritis. Issue 7 (28th May 2019) - Deodhar, Atul; Gensler, Lianne S.; Kay, Jonathan; Maksymowych, Walter P.; Haroon, Nigil; Landewé, Robert; Rudwaleit, Martin; Hall, Stephen; Bauer, Lars; Hoepken, Bengt; de Peyrecave, Natasha; Kilgallen, Brian; et al.
Abstract : Objective: The natural history of nonradiographic axial spondyloarthritis (SpA) is incompletely characterized, and there are concerns that nonsteroidal antiinflammatory drugs provide inadequate disease control in patients with active disease. This study was undertaken to investigate the effects of certolizumab pegol (CZP), an anti–tumor necrosis factor treatment, in patients with nonradiographic axial SpA with objective signs of inflammation. Methods: In this ongoing parallel‐group double‐blind study, adults with active disease were recruited from 80 centers in Australia, Europe, North America, and Taiwan, and were randomized 1:1 to receive placebo or CZP (400 mg at weeks 0, 2, and 4, followed by 200 mg every 2 weeks) in addition to nonbiologic background medication (NBBM). Switching to open‐label CZP (or other biologic) or making background medication changes was permitted at any point during the trial, although changes before week 12 were discouraged. The primary end point was the proportion of patients achieving major improvement (MI) (i.e., a ≥2.0‐point decrease in the score from baseline or achievement of the lowest possible score [0.6]) in the Ankylosing Spondylitis Disease Activity Score (ASDAS) at week 52. Results: A total of 317 patients were randomized to receive placebo plus NBBM (n = 158) or CZP plus NBBM (n = 159). ASDAS‐MI at week 52 was achieved in 47.2% (75 of 159) of CZP plus NBBM patients, which was significantly greater ( P < 0.0001) than the 7.0% (11 of 158) of placebo plus NBBM patients in whom ASDAS‐MI was achieved. Of the placebo plus NBBM patients, 60.8% (96 of 158) switched to open‐label treatment before week 52 compared to 12.6% (20 of 159) of the CZP plus NBBM patients. Conclusion: Adding CZP to background medication is superior to adding placebo in patients with active nonradiographic axial SpA. These results indicate that remission in nonradiographic axial SpA treated without biologics occurs infrequently, demonstrating the need for treatment beyond nonbiologic therapy. Abstract : Video Abstract Video Abstract